Hybrid Verbs of English Origin with the Suffix -inti Lithuanian Jargon: Morphology and Adaptive Features - Kudirka, Robertas (Lietuvių kalba, 2021)
The article analyses 198 hybrid verbs of English origin with the suffix -inti and 187 prefix derivatives from the Lithuanian slang and non-standard dictionary. The study reveals that borrows with affixal adaptation are always adapted to the linguistic system, because there weren’t any borrowed verbs without Lithuanian affix detected: phonetically adapted borrowed verbs from English are rare and used as adverbs. A small part of the verbs has no basic words, they are morphologically adapted with the suffix -inti. Word borrowing can be semantically based on the new meanings, but a number of verbs can be interpreted as trendy variants of non-standard language. Most of the verbs with the suffix -inti has basic words. The adaptation of the new borrowings is directly related with the popular suffixes of the Lithuanian standard language. Slang lexicon tends to copy standart language models and integrate into Lithuanian language derivative paradigms. Slang prefixes derived from basic verbs with the suffix -inti are formed regularly, slang derivatives take over the prefixes of the standard language.
Keywords: verbal borrowings; morphological adaptation; verbal derivation; slang